Pemberdayaan Kewirausahaan Ibu-Ibu Rumah Tangga Melalui Pelatihan Berbagai Makanan Ringan Sebagai Oleh-Oleh di Kelurahan KakaskasenDalam menunjang Kota Tomohon Sebagai Kota Wisata - HENDRA TAWAS (Universitas Sam Ratulangi, 2022)
The purpose of implementing this Community Service is to be able to provide new ideas about entrepreneurship for housewives and motivate housewives to want to become entrepreneurs. The target to be achieved is that the community becomes creative and can make snack products to be used as an entrepreneurial opportunity so that it can increase family income and be able to analyze the feasibility of entrepreneurship in making snacks. The results and outputs achieved by this service are the production of products that have economic value in the form of snacks for people who take part in the training to be motivated to become entrepreneurs and can improve the family economy. Keyword : housewives, entrepreneurship, snack